Islamic Cultures, Islamic Contexts: Essays in Honor of Professor Patricia Crone By Behnam Sadeghi, Asad Q. Ahmed, Adam Silverstein, and Robert Hoyland, eds. (Leiden: Brill, 2015. 631 pages.) (American Journal of Islam and Society, 2016)
This book is an important addition to the by-now rich collection of edited volumesand monographs published by Brill under the heading “Islamic Historyand Civilization: Studies and Texts.” It contains twenty-two essays written byleading scholars, historians, and philologists in honor of their late colleague and teacher Patricia Crone (professor of Islamic history, Institute for AdvancedStudy), who passed away a few months after the publication of the volume.For students of Islam, Crone needs no introduction. Her scholarship hasmarked the field through its erudition as well as its distinctive boldness andcontroversial nature that, at times, drew virulent criticism. Perceived by someas arrogant and hasty, by others as incisive and daring, she was not one tomince words. This volume, starting with an intimate “memoir” by Judith Herrinand concluding with an appreciative scholarly review by Chase Robinson,tends to overlook Crone’s divisive personality and does much to present heras an ideal academic and mentor. She was, as the editors lyrically phrase it, a“seeker and lover of truth.” ...